Effect of Hexane Addition on Mesoporous Silica Crystal Size Using Na2SiO3 from Chert Stone - Pera Meilita; Syamsi Aini; Fajriah Azra; Rahadian Zainul (Jurnal Periodic Jurusan Kimia UNP, 2022)
Mesoporous silica is a silica solid with pores between 2-50 nm which can be used in the fields of adsorption, medicine, catalyst synthesis, material purification and stationary phase for chromatography. Mesoporous silica is generally synthesized using TEOS or TMOS, but these precursors are relatively expensive. Na2SiO3 is a precursor of mesoporous silica which is more economical and easy to obtain. Basic materials that contain a lot of silica such as chert can be synthesized into Na2SiO3. Mesoporous silica synthesis generally uses surfactants as templates for the polymerization of silica, therefore a cosolvent is needed that can act as a crystal size enlarger by interacting with surfactants. The purpose of this study was to determine the effect of the addition of hexane on the synthesis of mesoporous silica symbolized by SM and SMH5. Mesoporous silica was synthesized using the sol-gel method with the basic ingredients of Na2SiO3 from chert, P104 as a surfactant, HCl as a solvent and n-hexane as an additive to increase crystal size. Mesoporous silica was characterized using XRD. The results of measurements using XRD showed that the X-ray difragtogram pattern showed peaks at an angle of 2ϴ = 22.29o and 25.33o for SM and SMH5 products, respectively.